Sacralism of Customary Law in Marriage: Local and National Legal Contestation in Indonesia - Novita Dewi Masyithoh; Maksun; Suteki; Muhammad Akmal Habib (Universitas Islam Negeri Walisongo Semarang, 2024)
Indonesia's legal framework has yet to formally recognize customary marriages within its Marriage Law, leaving indigenous communities without adequate legal protection despite their cultural and spiritual significance. Customary law communities, such as the Tengger community in Probolinggo and the Sedulur Sikep community in Pati, hold sacred beliefs and rituals tied to their ancestral heritage, resulting in a tension between customary and national legal systems. This study aims to address this gap by exploring the legitimacy of customary marriages and proposing legal reforms to accommodate their recognition. Using a qualitative descriptive approach, data were collected through observations, documentation, and interviews with members of the selected indigenous communities. The findings reveal three key insights: Indigenous communities adhere strongly to traditional marriage rituals as a continuation of ancestral values; the sacralism of customary marriage holds greater significance for these communities than national law, as it ensures legitimacy in the eyes of their ancestors; and the absence of legal recognition and protection for customary marriages by the state perpetuates legal and social marginalization. This study emphasizes the importance of adopting a legal pluralism perspective to bridge the gap between customary and national legal frameworks. It recommends reformulating Indonesia’s Marriage Law to include provisions recognizing the legitimacy and formal registration of customary marriages, ensuring harmony between cultural preservation and legal protection. Kerangka hukum Indonesia belum secara formal mengakui perkawinan adat dalam Undang-Undang Perkawinan, sehingga masyarakat adat tidak memiliki perlindungan hukum yang memadai meskipun mereka memiliki makna budaya dan spiritual. Komunitas hukum adat, seperti komunitas Tengger di Probolinggo dan komunitas Sedulur Sikep di Pati, memegang teguh kepercayaan dan ritual yang terikat pada warisan nenek moyang, sehingga menimbulkan ketegangan antara sistem hukum adat dan sistem hukum nasional. Studi ini bertujuan untuk mengatasi kesenjangan ini dengan mengeksplorasi legitimasi perkawinan adat dan mengusulkan reformasi hukum untuk mengakomodasi pengakuan mereka. Dengan menggunakan pendekatan deskriptif kualitatif, data dikumpulkan melalui observasi, dokumentasi, dan wawancara terhadap anggota komunitas adat terpilih. Temuan ini mengungkapkan tiga temuan utama: Masyarakat adat sangat memegang teguh ritual perkawinan tradisional sebagai kelanjutan nilai-nilai leluhur; sakralisme perkawinan adat mempunyai arti yang lebih penting bagi komunitas ini dibandingkan hukum nasional, karena hal ini menjamin legitimasi di mata nenek moyang mereka; dan tidak adanya pengakuan dan perlindungan hukum terhadap perkawinan adat oleh negara melanggengkan marginalisasi hukum dan sosial. Kajian ini menekankan pentingnya mengadopsi perspektif pluralisme hukum untuk menjembatani kesenjangan antara kerangka hukum adat dan kerangka hukum nasional. Artikel ini merekomendasikan perumusan ulang Undang-Undang Perkawinan Indonesia untuk memasukkan ketentuan-ketentuan yang mengakui legitimasi dan pencatatan formal perkawinan adat, memastikan keselarasan antara pelestarian budaya dan perlindungan hukum.